Wear behavior of plasma sprayed hydroxyapatite bioceramic coating in simulated body fluid. Issue 4 (March 2019) - Chen, Qing-Yu; Zou, Yan-Long; Fu, Wei; Bai, Xiao-Bo; Ji, Gang-Chang; Yao, Hai-Long; Wang, Hong-Tao; Wang, Fang
Abstract: To investigate the wear behavior of bioceramic coating, two-body abrasive wear of air-plasma sprayed (APS) hydroxyapatite (HA) coating was studied in different conditions including: i) in simulated body fluid (SBF) and in dry conditions, and ii) sliding on Al2 O3 abrasive paper, HA, polycarbonate (PC) and polyurethane (PU), as well as iii) on different applied loads. Cross-sectional microstructures and worn surface morphologies of the coating were examined by scanning electron microscopy (SEM). Phase constitutions were analyzed by X-Ray diffraction (XRD). Microhardness, elastic modulus, fracture toughness and bond strength of the coating were investigated. It was revealed that, under the load of 20 N and sling on different counterpart materials, the wear rates of the coating varied from 24.09 × 10 −2 to 0.25 × 10 −2 mg/Nm in SBF and varied from 13.54 × 10 −2 to 0.05 × 10 −2 mg/Nm in dry condition, respectively. The accumulated weight loss of the coating sliding on HA in SBF increased from 3.1 to 7.9 mg as the applied load increased from 5 N to 20 N. As sliding on Al2 O3 in dry condition and/or under high load, the abrasive wear of the coating dominantly occurred in the form of ploughing and peeling off of splats. As sliding on PC, PU and HA in SBF, the adhesive wear of the coating mainly occurred in the form of exfoliation.